Discursive Leadership: In Conversation With Leadership Psychology - Gail T. Fairhurst (Sage, 2007)
Discursive Leadership: In Conversation with Leadership Psychology presents a new, groundbreaking way for scholars and graduate students to examine and explore leadership. Differing from a psychological approach to leadership which tries to get inside the heads of leaders and employees, author Gail Fairhurst focuses on the social or communicative aspects between them. A discursive approach to leadership introduces a host of relatively new ideas and concepts and helps us understand leadership′s changing role in organizations.